2023
DOI: 10.3390/nu15183986
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of European Clinical Trials Characterizing the Healthy-Adult Serum 25-hydroxyvitamin D Response to Vitamin D Supplementation

Manuel Rupprecht,
Stefan Wagenpfeil,
Jakob Schöpe
et al.

Abstract: To obtain reliable data that allow health authorities to re-evaluate recommendations for oral vitamin D uptake, we conducted a meta-analysis to investigate the impact of supplementation on serum 25-hydroxyvitamin D (25(OH)D) levels in healthy adults in Europe. Of the publications identified (n = 4005) in our literature search (PUBMED, through 2 January 2022), 49 primary studies (7320 subjects, 73 study arms) were eligible for inclusion in our meta-analysis. The risk of bias was assessed using the Cochrane RoB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…One recent recommendation for VD supplementation for all healthy adults in Europe is approximately 1000 IU daily. This would raise the VD serum levels in 95% of the population to >50 nmol/L [ 34 ]. In another systematic review, data confirmed that keeping the VD serum concentrations above 50 ng/mL (125 nmol/L) reduces the risk from community outbreaks, sepsis and autoimmune disorders [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One recent recommendation for VD supplementation for all healthy adults in Europe is approximately 1000 IU daily. This would raise the VD serum levels in 95% of the population to >50 nmol/L [ 34 ]. In another systematic review, data confirmed that keeping the VD serum concentrations above 50 ng/mL (125 nmol/L) reduces the risk from community outbreaks, sepsis and autoimmune disorders [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…These differences in dosage recommendations highlight the need among both healthy and diseased human beings for monitoring VD serum levels and correspondingly adjusting VD dosage. Only when reaching an individual proper dose of VD can effectiveness be ensured and any adverse effects due to overdosing be avoided [ 34 ]. Besides finding the correct dosage of VD, the mode of supplementation also plays a critical role.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, numerous studies have been conducted on the effects of vitamin D on the human body [1][2][3]. Previous research has revealed its significant impact on calcium-phosphate metabolism of the body's skeletal system [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…25 hydroxyvitamin D (25(OH)D) is a fat-soluble vitamin that, when converted into its biologicallyactive form, 1,25-dihydroxyvitamin, influences the expression of over 900 genes [6,8,9]. These genes impact a wide variety of health and performance aspects, such as the immune and endocrine systems, exercise-induced inflammation, cardiovascular health, cancer prevention, neurological function, glucose metabolism, as well as bone and muscle structure and metabolism [3,6,8,10,11]. Vitamin D also has a significant impact on mental health, including depression, cognitive disorders, and neurological impairments [1,3,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation